ChemInform Abstract: Biologically Driven Synthesis of Pyrazolo[3, 4‐d]pyrimidines as Protein Kinase Inhibitors: An Old Scaffold as a New Tool for Medicinal Chemistry and Chemical Biology Studies. Issue 40 (30th September 2014) - Schenone, Silvia; Radi, Marco; Musumeci, Francesca; Brullo, Chiara; Botta, Maurizio
Abstract Review: 251 refs.